1997
DOI: 10.1111/j.0022-3646.1997.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH‐CONTROLLED OSCILLATION IN ACTIVITY OF HISTONE H1 KINASE DURING THE CELL CYCLE OF CHLAMYDOMONAS REINHARDTII (CHLOROPHYTA)1

Abstract: Synchronous cultures of the cell wall-less mutant Chlamydomonas reinhardtii Dangeard cw 15 were grown under different mean irradiances and dzffent illumination regimes, which produced cell cycles that dflered in the number of daughter cells released from one mother cell, in the length Ofthe cell cycle, and in the growth rate. During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…1). The change in cell density over this growth period fit a sigmoidal function (r 2 = 0.94, 0.91 and 0.7 for P, PA and PAB, respectively), similar to those described in the literature for synchronized cells (Zachleder et al 1997).…”
Section: Resultssupporting
confidence: 75%
“…1). The change in cell density over this growth period fit a sigmoidal function (r 2 = 0.94, 0.91 and 0.7 for P, PA and PAB, respectively), similar to those described in the literature for synchronized cells (Zachleder et al 1997).…”
Section: Resultssupporting
confidence: 75%
“…It has been shown that phosphorylation of CDK-like protein(s) as well as its activity oscillates during the cell cycle, peaking at the attainment of commitment points and at the time when nuclear and cellular divisions are performed (John et al 1989;Zachleder et al 1997;Bišová et al 2000). Recently it was found that C. reinhardtii encodes orthologues of the major plant CDK and cyclin families (Bišová et al 2005).…”
Section: Chlamydomonas Reinhardtii Cell Cyclementioning
confidence: 99%
“…C.P. : commitment point; G1, S, G2, M: phases of the common cell cycle; "G1": G1-like phase after the cells passed commitment; G3: gap phase separating nuclear and protoplast divisions in Scenedesmus cell cycle (Zachleder et al 1997); C: cytokinesis , C. reinhardtii cell culture can be synchronized so that > 95% of cells proceed through three rounds of mitosis within 4-5 h. The inhibitors routinely used for synchronization of plant cells provide an addi-356 K. Bišová tional means to manipulate the outcome of the cell cycle (see below). Of the species described below, C. reinhardtii is the best established model system for genetics with an improving molecular toolkit (Harris 2001).…”
Section: Multiple Fission: a Variation On The Themementioning
confidence: 99%
“…The postcommitment period is an equivalent of late G1 phase; late G1 phase is the period when the origins of replication become licensed for replication and S phase CDKs become activated (Nasmyth 1996). It has been proposed to call this phase pre-S (pre-synthetic) in algal cell cycles (Zachleder et al 1997). …”
Section: The Chlamydomonas Reinhardtii Cell Cyclementioning
confidence: 99%
See 1 more Smart Citation